Methods of a national survey of young Aboriginal and Torres Strait Islander people regarding sexually transmissible infections and bloodborne viruses. (10th August 2015) - Ward, James; Bryant, Joanne; Wand, Handan; Kaldor, John; Delaney‐Thiele, Dea; Worth, Heather; Betts, Sarah; Waples‐Crowe, Peter; Cairnduff, Sallie; Coburn, Tony; Donovan, Basil; Pitts, Marian
Abstract: Objective: To describe the methods and basic demographics of participants in a national survey of Aboriginal and Torres Strait Islander (Aboriginal) people specific to sexually transmissible infections and bloodborne viruses. Methods: A national cross‐sectional survey of Aboriginal people aged 16–29 years in all Australian jurisdictions between 2011 and 2013 conducted at Aboriginal community events. Questions comprised demographic information, knowledge, risk behaviours and health service utilisation. Questionnaires were completed on personal digital assistants (PDAs). Results: A total of 2, 877 people at 21 unique community events completed the questionnaire. A total of 59% of participants were female, median age was 21 years and more than 60% were single at the time of the survey. Just over half the participants were resident in an urban area (53%) and 38% were from a regional area. Aboriginal health organisations played an important role in implementing the research. PDAs were found to be an acceptable method for collecting health information. Conclusion: This survey has recruited a large representative sample of Aboriginal people aged 16–29 years using a methodology that is feasible, acceptable and repeatable. Implications: The methodology provides a model for ongoing monitoring of this population as programs and policies are implemented to address young Aboriginal people's STI and BBV risks.